Study of Shamanic Witchcraft (Santet) Culture in the Indonesian Archipelago - Risma, Olivia (Enigma Institute, 2023)
Various ethnic groups in Sumatra also possess shamanic traditions that involve traditional rites and the involvement of shamans or individuals with specialized skills in countering black magic. Each of these ethnic groups possesses distinct practices and beliefs. The Batak tribe has diverse ethnic subgroups, including Toba Batak, Karo, Mandailing, and others. Within Batak culture, there exist shamanistic rituals, and individuals who perform these rituals are referred to as